Tyrosine kinase inhibitors in patients with neuroendocrine neoplasms: a systematic literature review - Rodrigo G. Taboada; Felicia P. Cavalher; Juliana F. Rego; Rachel P. Riechelmann (Therapeutic Advances in Medical Oncology)
Background: Several tyrosine kinase receptors inhibitors (TKIs) have demonstrated antiproliferative effects in well-differentiated neuroendocrine tumors (NETs). We aimed to summarize and appraise the current evidence of the efficacy of TKIs in patients with different types of NETs. Methods: We performed a systematic review of clinical trials of TKIs in patients with advanced gastroenteropancreatic or lung NETs (PROSPERO registration number: CRD42024507379). Population characteristics, efficacy, and safety results were summarized by type of NET. Results: Twenty-eight studies were eligible, totaling 2284 patients. While sunitinib remains the only Food and Drug Administration-approved TKI in patients with NETs (for patients with pancreatic well-differentiated NETs), recent placebo-controlled randomized trials have demonstrated improved response rates and progression-free survival for patients with progressive and pre-treated well-differentiated pancreatic (cabozantinib or surufatinib) or gastrointestinal (GI) NETs (pazopanib, cabozantinib, or surufatinib). There is limited evidence to support the use of a TKI in patients with lung or grade 3 NETs. The toxicity associated with TKIs follows a class effect, with a significant proportion of patients experiencing fatigue, hypertension, and hand–foot skin reactions. Conclusion: TKIs are effective therapies in patients with pancreatic or GI well-differentiated NETs and should be part of the therapeutical sequencing of these patients.